THERMOPLASTIC MATERIALS - A NEW STAGE IN THE LIFE OF AIRCRAFT CONSTRUCTION - Teplyk, Yevgenii; Hapon, Viacheslav; Tuz, Mykola (Proceedings of National Aviation University (archive), 2020)
Purpose: The main purpose of this article is to update the processes of using thermoplastic materials in modern aircraft structures of aircraft. Results: The result of the analysis of the modern market for aviation technologies and aviation materials is the active use of thermoplastic materials in the structures of aircraft of leading manufacturers in the field of aircraft construction. Discussion: The introduction of technologies for using composite thermoplastic materials in aerospace structures by foreign aviation enterprises is characterized.